2008
DOI: 10.1007/s12206-008-0622-3
|View full text |Cite
|
Sign up to set email alerts
|

Lie group analysis of radiation natural convection heat transfer past an inclined porous surface

Abstract: Natural convection heat transfer fluid flow past an inclined plate embedded in a fluid-saturated porous medium is investigated by Lie group analysis. The governing partial differential equations are reduced to a system of ordinary differential equations by the scaling symmetries. From numerical results, it is found that the thermal and momentum boundary layer thicknesses are increased as the radiation parameter is increased. Also, it is observed that the velocity is increased and the temperature is decreased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Because of these applications, several researchers engage with analyzing the heat transfer process in di erent physical contexts. Some of the important studies that underline such concept can be found in references [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these applications, several researchers engage with analyzing the heat transfer process in di erent physical contexts. Some of the important studies that underline such concept can be found in references [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Bhuvaneswari et al [20] mentioned that the study of convective energy transport involved in the occurrence of thermal radiation has been brought into many scholars' attention due to its wide range of applications. Lee et al [21] used Lie group analysis to investigate the e ect of radiation on free convection ow past an inclined plate in a saturated porous medium. The e ects of radiation and Hall currents on MHD ow over a plate were investigated by Das et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…They noticed that the local skin friction decreases and local heat transfer increases upon the increase of the radiation parameter. Lee et al [12] and Bhuvaneswari et al [13] also explored free convection and heat transfer of an incompressible uid with radiation e ect in a porous medium. The combined MHD convection of an incompressible uid with heat generation and radiation at a stagnation-point was studied by Makinde [14] and Hayat [15].…”
Section: Introductionmentioning
confidence: 99%